2014
DOI: 10.1016/j.procir.2014.03.145
|View full text |Cite
|
Sign up to set email alerts
|

Design for Additive Manufacturing – Supporting the Substitution of Components in Series Products

Abstract: The Additive Manufacturing technologies Selective Laser Sintering (SLS) and Selective Laser Melting (SLM) are capable to produce thermoplastic or metal parts, which are fit for end-user products. Both technologies create three-dimensional objects directly from a 3D CAD model with little restrictions regarding the shape of the object. This geometrical freedom in design can be utilized to largely improve the functionality of series products by substituting conventional parts with additive manufactured ones. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 7 publications
1
54
0
Order By: Relevance
“…This step aims to establish which components would in some sense gain from being manufactured using additive manufacturing Klahn et al (2014) have identified four types of components: 1 components where AM would bring benefits; 2 components where AM could bring benefit but risks and expectations have to be further evaluated; 3 components where no benefits of using AM are expected; and 4 components where AM could not be used as a manufacturing method.…”
Section: Choose Component For Additive Manufacturingmentioning
confidence: 99%
“…This step aims to establish which components would in some sense gain from being manufactured using additive manufacturing Klahn et al (2014) have identified four types of components: 1 components where AM would bring benefits; 2 components where AM could bring benefit but risks and expectations have to be further evaluated; 3 components where no benefits of using AM are expected; and 4 components where AM could not be used as a manufacturing method.…”
Section: Choose Component For Additive Manufacturingmentioning
confidence: 99%
“…Klahn et al [24] suggested two kinds of design strategies for AM; 'manufacturing-driven design strategy ' and 'function-driven design strategy '. The former strategy kept in view the manufacturer's perspective which followed certain design rules to mass customize a part by preserving the conventional design, while the latter strategy envisioned the designer's perspective and improved the function of a product as worked upon by Klahn et al [25] for a medical device used in shockwave therapy. Rapid prototyping itself is a great example of utilizing AM's process advantages by considering a part which is designed for conventional production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The surface finish of additive manufactured parts can be controlled through the proper selection of process parameters, part orientation and material selection. Furthermore, as indicated by Klahn et al [16], additive manufacturing cannot be considered to replace conventional manufacturing processes, but should be considered when the 9 design goal is to develop products that present either of the following criteria: integrated design, individualization, lightweight design and efficiency.…”
Section: Additive Manufacturing Guidelinesmentioning
confidence: 99%